Visible spectrophotometric method for determination of enzalutamide in bulk and formulation dosage - DR.L.SATYANNARAYANA; T.PADMINI (International Journal of Pharma and Bio Sciences, 2017)
Enzalutamide is an oral non-steroidal anti-androgen used for the treatment of prostate cancer. It is commercially available as XTANDI®. No visible spectrometric method has been reported for estimation of enzalutamide in formulation sample. In the present work, two visible spectrophotometric methods have been developed for quantitative determination of enzalutamide in bulk drug and formulation samples. These methods are validated for irinotecan with two chromogenic reagents namely 1,2 naphthoquinone-4-sulphonic acid (NQS),3-methyl benzothiazolinone hydrazine (MBTH) at λmax of 630nm and 453nm respectively. The calibration curves were linear over a concentration range from 10-60 µg/ml for method 1 and 2.5-25 µg/ml for method 2. The relative standard deviations were less than 1% and average recovery was above 99.60%.These visible spectrophotometric methods at the respective absorption maxima enabled determination of the drug with no interference from the excipients.